2006
DOI: 10.1063/1.2364897
|View full text |Cite
|
Sign up to set email alerts
|

Effective molecular polarizabilities and crystal refractive indices estimated from x-ray diffraction data

Abstract: Articles you may be interested inAlthough it was proposed some time ago that ͑hyper͒polarizabilities might be estimated from the results of x-ray charge density refinements, early results were unconvincing. In this work we show that the one particle density obtained from the usual multipole refinement model does not contain sufficient information to determine these response properties and instead pursue the "constrained wave function" approach of fitting to x-ray structure factors. Simplified sum-over-states e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 72 publications
(112 reference statements)
4
60
0
Order By: Relevance
“…However, application of this method to organic non-linear optical materials revealed that many components of α and β tensors, calculated from X-ray diffraction, differ by more than an order of magnitude from theoretical results. Indeed, it was later shown that the one-electron density ρprq, obtained from the usual multipolar pseudo-atom formalisms, does not yield accurate response properties because electronic correlation is included only partially [22]. Instead, Jayatilaka and Cole [23] have pursued an X-ray constrained wavefunction approach to derive much more accurate ρprq distributions for a few optical materials, including a metal-organic non-linear optical compound.…”
Section: From Functional Groups and Molecules To Crystalsmentioning
confidence: 99%
“…However, application of this method to organic non-linear optical materials revealed that many components of α and β tensors, calculated from X-ray diffraction, differ by more than an order of magnitude from theoretical results. Indeed, it was later shown that the one-electron density ρprq, obtained from the usual multipolar pseudo-atom formalisms, does not yield accurate response properties because electronic correlation is included only partially [22]. Instead, Jayatilaka and Cole [23] have pursued an X-ray constrained wavefunction approach to derive much more accurate ρprq distributions for a few optical materials, including a metal-organic non-linear optical compound.…”
Section: From Functional Groups and Molecules To Crystalsmentioning
confidence: 99%
“…However, as already observed by Jayatilaka and co-workers Whitten et al, 2006;Jayatilaka et al, 2009;Hudá k et al, 2010), the convergence towards the desired agreement is not always fast and straightforward. In order to avoid large values of producing only minimal improvements in the 2 statistics and large unphysical changes of the energy, the following termination criteria have recently been proposed (Genoni, 2013b):…”
Section: X-ray Constrained Extremely Localized Molecular Orbitalsmentioning
confidence: 85%
“…Therefore, for a definitive and fair comparison with the traditional multipole models, we should push the X-ray constrained computations beyond the usual 2 ¼ 1:0 limit (namely, we should consider larger ). Whitten et al (2006) have proposed pursuing the fitting until the weighted residual wR values approach those obtained in the multipole refinement of the same X-ray structure-factor magnitudes. This idea could be reformulated using 2 as a criterion, but, unfortunately, this is partially hampered by the problem of determining the optimal value for the Lagrange multiplier (see final discussion in x3.2).…”
Section: Discussionmentioning
confidence: 99%
“…A correction is necessary, however, in order to include the long range effects of a periodic distribution of polarizable building blocks, as suggested by Dunmur [48] and adopted by Spackman et al [49]. This means that each BB polarizability should be corrected for the apparent enhancement, caused by the electric field of the induced dipole moments of all other building blocks in the crystal.…”
Section: Propertiesmentioning
confidence: 99%